PENERAPAN METODE BERCERITA BUKU PILAR KARAKTER HORMAT, SANTUN DAN PENDENGAR YANG BAIK UNTUK MENINGKATKAN KEMAMPUAN SOSIAL EMOSIONAL ANAK KELOMPOK A1 DI RA SYIHABUDDIN KECAMATAN DAU KOTA MALANG - Nuzula Mardiyah; Ika Ratih Sulistiani; Ika Anggraheni (Jurnal Dewantara, 2020)
It was also revealed that in recent years the culture of hospitality and courtesy in Indonesia has increasingly disappeared. Efforts were made to improve social emotional capacity by providing character learning through the story telling method of the 4 pillar characters of respect, courtesy and good listeners. This type of research used isClassroom Action Research. This research was conducted at RA SYIHABUDDIN on students in group A1.There was a very significant increase in cycle II week II, most children occupy success rates of 86% -100%, amounting to 12 children. It can be concluded that learning in improving children's emotional emotional abilities by reading a book 9 pillars of character 4 with the title Respect, Courtesy and Good Listener can improve and enhance the emotional social abilities of early childhood. Storytelling and simulation are a unity that must be done because children not only imagine, but also practice, so they will always be remembered until adulthood and become a provision in the future.